Study of gliclazide solid dispersion systems using PVP K-30 and PEG 6000 by solvent method - Febriyenti Febriyenti; Suraiya Rahmi; Auzal Halim (Wolters Kluwer Medknow Publications, 2019)
Gliclazide is a second-generation hypoglycemic sulfonylurea, which is useful in the treatment of non-insulin-dependent diabetes mellitus. It has low bioavailability because of its limited water solubility and slow dissolution rate. In this study, solid dispersions of gliclazide were prepared by solvent method. Drug and carriers weight ratio were 1:9; 2:8; 3:7; 4:6; and 5:5. The weight ratio of carriers (polyvinyl pyrrolidone K-30 and polyethylene glycol 6000) was 1:1. The properties of solid dispersions were evaluated using scanning electron microscopy (SEM), Fourier-transform infra red (FTIR) spectroscopy, differential scanning calorimetry (DSC), X-ray diffraction (XRD), and solubility and dissolution studies. SEM result showed that gliclazide was highly dispersed and was present as amorphous state in the solid dispersions. The FTIR spectroscopy showed no chemical interaction between gliclazide and carriers. DSC studies indicated melting point of gliclazide was decreased. The XRD studies indicated that crystallinity degree of gliclazide was decreased. Rate of dissolution and solubility of solid dispersions was increased than pure gliclazide (F < 0.05).